Process Optimization for development of low calorie milk cake - Kumar, Arvind; Singh, Ranjeet Pratap; Pandhi, Shikha (Indian Journal of Dairy Science, 2019)
Among the indigenous dairy products, khoa and khoa based milk sweets have served as a good means of conserving and safeguarding surplus milk solids. Milk cake is the most popular heat desiccated milk based sweet which is characterized by its well-defined grainy texture and pronounced caramel flavor. In the present study, an attempt was made to develop a low-calorie milk cake with the incorporation of artificial sweetener and fat replacer in the milk using Response Surface Methodology and also, to study various physiochemical parameters of the optimized product. An RSM experiment was conducted with three variables viz., Milk Fat (1.0-3.0%), Aspartame (0.3-0.5%) and Gum Acacia (0.3-1.0%). The average value of proximate chemical analysis of fat, protein, added sugar, moisture and ash was 5.30%, 17.31%, 0.00%, 17.23%, and 2.37% respectively. Results showed that the level of fat and carbohydrate was decreased drastically, and helped in reducing the calorific value of milk cake. The energy value of low-calorie milk cake was reduced about half of the market milk cake as the energy value of low-calorie milk cake was 3.782 kcal/gm and market milk cake was 6.335 kcal/gm.